CLARK W. BEASLEY (1942–2012) - Mcinnes, Sandra J. (Zootaxa, 2013)
Clark Wayne Beasley was born in Pittsburg, Kansas, USA on 6 June 1942. He graduated from Kansas State College of Pittsburg in 1964 and went on to successfully defend his PhD on the tardigrades of Oklahoma in 1968 at the University of Oklahoma. Clark moved to McMurray College in 1969 to become an Assistant Professor in the Department of Biology, accepting the chair in 1973 as an Associate Professor, became a full Professor in 1977 and Distinguished Professor in 1999. He was awarded the McMurray College “Gordon and Lola Bennett Scholar Award” in 2009 in recognition of his continuing contributions to outstanding teaching, scholarship, and service to the university. Clark retired in 2010.